EAM-LoRaNet: Energy Aware Multi-hop LoRa Network for Internet of Things - Misbahuddin Misbahuddin; Muhammad Syamsu Iqbal; Djul Fikry Budiman; Giri Wahyu Wiriasto; Lalu Ahmad Syamsul Irfan Akbar (Universitas Muhammadiyah Malang, 2022)
LoRa Technology is one of the devices used on Low-Power Wide Area Networks (LPWAN), which is a viable alternative wireless communication technology for the Internet of Things (IoT). The LoRa device is meant to traverse a large distance while using minimal power. However, because it uses single-hop communication, the Gateway's farthest nodes will die prematurely as a result of the increased energy usage. This research attempts to improve the range of LoRa networks utilizing multi-hop uplink communication while also reducing energy consumption by adjusting the LoRa transmission power to the lowest possible dBm in each hop. As a network model, a star topology-based tree made of some rings with a gateway as the central point is chosen. The performance of two forms of uplink communication, single-hop and multi-hop models was tested in terms of energy consumption and coverage. The results show that the network structure in the multi-hop uplink model can extend coverage over a greater distance while using less energy than the single-hop uplink model. This model can be used as a supplement to the LPWAN's uplink communication in the IoT to enhance the network's coverage range and lifetime.